PRACTICAL RECOMMENDATIONS FOR THE IMPLEMENTATION OF AUDITING ACTIVITIES BASED ON THE EXISTING DOCUMENT DOCUMENTS "PROFESSIONAL STANDARD" AUDITOR ". - Urakova M.H; Tairova M.M (Scholar Express Journals, 2021)
The draft "Professional standard auditor" in the Republic of Uzbekistan is still at the stage of development and approval. The purpose of developing this professional standard is to consolidate the auditor's profession in the regulatory framework, to attract qualified specialists to work and to increase the level of professional competence of auditors. The approval of the professional standard "auditor" will allow to systematize the existing requirements for the level of necessary knowledge, skills and abilities of auditors, will also make it possible to widely use professional potential to improve the efficiency of management of Uzbek companies, create a basis for the development of educational standards and the introduction of an audit course in higher professional institutions for training of highly qualified specialists. Timely implementation and development of this standard will undoubtedly contribute to the development of a systematic and integrated approach to auditing in the Republic of Uzbekistan. Similar standards already exist for accountants, company managers and others. Professional standards significantly improve the image of the profession and help attract young professionals
Keywords: Audit; economics; Professions; description